Flood relief and rehabilitation in Ormoc experiences and insights of administrators - De Leon, Corazon Alma G.; Laigo, Lina B. (1993)
The extent and magnitude of damages wrought by the flood that struck Ormoc City in 1992 were beyond what the relief and rehabilitation agencies could handle. The impact of the disaster was aggravated by the failure to detect its coming as well as the lack of mitigation measures, rendering both the government and the people unprepared for the disaster. An account of how the Ormoc City Tragedy was handled has generated inputs and policy recommendations on disaster management by which to prevent similar experiences in the future.
Keywords: Floods -- Ormoc City (Leyte) -- Risk assessment; Emergency management -- Ormoc City (Leyte); Ormoc Disaster, 1992